The Effects of Angle of Attack, Aspect Ratio, and Leading-Edge Curvature on Supersonic Fin Performance - Shiddieqy, M. Hasbi Ash; Andoko, Andoko (Andalasian International Journal of Applied Science, Engineering and Technology, 2025)
The aerodynamic optimization of fin-stabilized rockets operating under supersonic conditions remains a critical challenge in aerospace enginnering. Current studies often fail to capture the combined effects of multiple geometric parameters on aerodynamic performance. This research employs a full-factorial design of experiments (DoE) integrated with computational fluid dynamics (CFD) simulations using the k-w SST turbulence model to evaluate the influence of angle of attack (AoA), fin aspect ratio, and leading-to-drag ratios, with higher AoA increasing lift but also inducing drag penalties. Contrary to conventional assumptions, lower aspect ratios (around 0.3) produced higher lift, while increasing aspect ratio resulted in more complex shock interactions and drag rise. A progressive increase in leading-edge curvature improved lift and reduced drag, with the best performance observed at curvatures around 30-40 mm. These findings highlight the critical role of geometric configuration in managing supersonic aerodynamic behavior, including shock wave formation, boundary layer dynamics, and vortex control. The study provides a comprehensive framework for optimizing fin geometry to enhance aerodynamic efficiency in high-speed flight.